Global and Regional Estimates for Subtype-Specific Therapeutic and Prophylactic HIV-1 Vaccines: A Modeling Study - Ramyiadarsini Elangovan; Michael Jenks; Jason Yun; Leslie Dickson-Tetteh; Shona Kirtley; Joris Hemelaar; WHO-UNAIDS Network for HIV Isolation and Characterisation; Alash’le G Abimiku; Simon Agwale; Chris Archibald; Boaz Avidor; María Gabriela Barbás; et al. (Frontiers in Microbiology, 2021)
Global HIV-1 genetic diversity forms a major obstacle to the development of an HIV vaccine. It may be necessary to employ subtype-specific HIV-1 vaccines in individual countries according to their HIV-1 subtype distribution. We estimated the global and regional need for subtype-specific HIV-1 vaccines. We took into account the proportions of different HIV-1 variants circulating in each country, the genetic composition of HIV-1 recombinants, and the different genome segments (gag, pol, env) that may be incorporated into vaccines. We modeled different scenarios according to whether countries would employ subtype-specific HIV-1 vaccines against (1) the most common subtype; (2) subtypes contributing more than 5% of HIV infections; or (3) all circulating subtypes. For therapeutic vaccines targeting the most common HIV-1 subtype in each country, 16.5 million doses of subtype C vaccine were estimated globally, followed by subtypes A (14.3 million) and B (4.2 million). A vaccine based on env required 2.6 million subtype E doses, and a vaccine based on pol required 4.8 million subtype G doses. For prophylactic vaccines targeting the most common HIV-1 subtype in each country, 1.9 billion doses of subtype A vaccine were estimated globally, followed by subtype C (1.1 billion) and subtype B (1.0 billion). A vaccine based on env required 1.2 billion subtype E doses, and a vaccine based on pol required 0.3 billion subtype G doses. If subtype-specific HIV-1 vaccines are also directed against less common subtypes in each country, vaccines targeting subtypes D, F, H, and K are also needed and would require up to five times more vaccine doses in total. We conclude that to provide global coverage, subtype-specific HIV-1 vaccines need to be directed against subtypes A, B, and C. Vaccines targeting env also need to include subtype E and those targeting pol need to include subtype G.